2006 IEEE International Conference on Industrial Technology 2006
DOI: 10.1109/icit.2006.372690
|View full text |Cite
|
Sign up to set email alerts
|

A New Wireless-Type Physiological Signal Measuring System Using a PDA and the Bluetooth Technology

Abstract: A light and portable-type wireless physiological Concering the application of wireless transmissions in the signal retrieving system has always been a medical personnel's dream. To fulfill this dream, this paper investigates a feasible medical care, Pavlopoulos, et al. [1] installed GSM method to create a wireless-type physiological signal measuring communication systems inside ambulances to transmit vital system using a PDA and the bluetooth technology. The proposed physiological signals, such as electrocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In the literature, electronic stethoscope had been implemented by using general-purpose microcontrollers (MCUs) [ 2 5 , 9 ], DPS chips [ 1 , 7 , 8 ], or even ASIC chips [ 6 ]. We chose to build the proposed prototype of ALE circuit using FPGAs instead.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, electronic stethoscope had been implemented by using general-purpose microcontrollers (MCUs) [ 2 5 , 9 ], DPS chips [ 1 , 7 , 8 ], or even ASIC chips [ 6 ]. We chose to build the proposed prototype of ALE circuit using FPGAs instead.…”
Section: Methodsmentioning
confidence: 99%
“…However, albeit basic, stethoscope is still essential for the diagnoses of many diseases. In fact, the electronic stethoscope is one medical instrument studied recently by many groups of researchers [ 1 – 9 ]. Numerous new features were studied, and some of them are made commercially available [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A portable phonocardiography (PCG), electrocardiography, and body temperature measurement system prototype is described in [37]. It is controlled by a personal digital assistant (PDA) with an external memory unit and consists of a capacitor-type microphone inserted on a stethoscope for PCG detection, a three-lead ECG, a temperature sensor, a measuring board including a central processing unit (CPU), a Bluetooth transceiver, and an analog and digital (A/D) module.…”
Section: System Prototypes and Functionalitiesmentioning
confidence: 99%
“…As part of a review of body‐worn health monitoring systems, including the survey of Pantelopoulos and Bourbakis [7, 9–13], 24 commercial and academic systems were analysed. This review indicated that no system for use in an emergency setting involved highly synchronised multi‐channel auscultation.…”
Section: Related Workmentioning
confidence: 99%